PENGARUH AKTIVITAS IBU RUMAH TANGGA DI LUAR RUMAH TERHADAP KEHIDUPAN KELUARGA DI DESA RAWANG SARI KECAMATAN PANGKALAN LESUNG KABUPATEN PELALAWAN - Siti Halimah Tusadiah; Ashaluddin Jalil (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This study aims to determine the role of housewives in meeting the economic needs of families in Rawang Sari Village, Pangkalan Lesung District, Pelalawan Regency and to determine the impact of the dual roles of housewives on household life in Rawang Sari Village, Pangkalan Lesung District, Pelalawan Regency. This study uses a type of descriptive qualitative approach. In this study using data analysis techniques such as data reduction, data collection, data presentation, and drawing conclusions. Based on the results of the study, it can be concluded that the involvement of women in helping the family economy is by providing opportunities for housewives in the form of trade knowledge possessed, skills possessed, and the ability to work in other places and the impacts that arise include positive and negative impacts. Such positive impacts can help meet the economic needs of the family, can improve status in the family, and build a sense of mutual understanding between family members. The negative impact is that the social impact will be felt by children, attention and affection from their mothers will be reduced, and attention in terms of education will also be greatly reduced because both fathers and mothers work outside the home. Keywords: Women, Family Economy, Welfare